Tethered Spinal Cords - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1989)
The diagnosis of tethered spinal cord by MRI in seven children with cutaneous lumbar hemangioma is reported from the Children's Hospital of Pittsburgh, University of Pittsburgh School of Medicine.